Young people's presents and futures, and the moral obligation to be enterprising and aspirational in times of crisis. (March 2023) - Goring, James; Kelly, Peter; Carbajo, Diego; Brown, Seth
Abstract: In this paper we reference a recent OECD report, Dream Jobs? which argues that education systems should guide young people's aspirations for their futures in ways that counter negative misalignment with the jobs of the future. We situate an analysis of this report in the development of our concept of global grammars of enterprise (GGE) to analyse the vocabularies and norms that structure contemporary obligations for young people to be 'enterprising' and 'aspirational' in the context of multiple crises. In developing this critical sociological analysis we tell the stories of three young people from a larger project in Melbourne (AUSTRALIA), that reveal the complexity of young people's presents, and the relationships of these presents to young people's aspirations. Deploying Appadurai's concept of the capacity to aspire, and Foucault's work on the care of the self, we argue that in GGE the vocabulary of aspiration can be understood as a 'moral disposition' that young people should develop to relationships between presents and futures. In the context of multiple crises, we suggest that young people's aspirations should be re-imagined as a complex and ambivalent mélangé of hopes, despair and desires that is only partly concerned with their education and employment pathways. Highlights: Global grammars of enterprise encourage young people to be aspirational. Aspirations are understood largely in terms of the future of work and career choices. The grammars construct a moral obligation to be aspirational in particular ways. For many young people their sense of the future is more complex, uncertain and ambiguous. Young people's capacities to aspire need to be understood in more cultural and contextual ways.